Crop responses to topsoil replacement within eroded landscapes. (6th May 2021) - Schneider, Sharon K.; Cavers, Curtis G.; Duke, Sara E.; Schumacher, Joseph A.; Schumacher, Thomas E.; Lobb, David A.
Abstract: Approaches to restore productivity to eroded soils are urgently needed to sustain food security. We evaluated plant response to soil‐landscape rehabilitation, in which approximately 15 cm of topsoil was moved from depositional landscape positions to the eroded upper slope. Crop response was monitored for 6 yr of a corn ( Zea mays L.)–soybean [ Glycine max (L.) Merr.] rotation at a severely eroded site and for 4 yr of a wheat ( Triticum aestivum L.)–soybean rotation at a moderately eroded site. Experiments were conducted in years with relatively wet springs and droughty summers. In the severely eroded landscape, addition of 15 cm of soil increased crop biomass by 25–95% on a kg ha –1 basis and increased grain yields by 20–49% (corn) and 12–59% (soybean), with the largest yield increases recorded in the most eroded landscape positions. Soil addition increased corn grain protein and test weight. No significant differences were observed in crop emergence rate or stand establishment. In the moderately eroded landscape, soil addition significantly increased crop biomass, but not grain yield. In both landscapes, yields were lower in areas of soil removal than in adjacent areas from which no soil was removed, which is likely at least partially an artifact of the plot design. While more research is needed to evaluate long‐term impacts, the results of these studies show that soil‐landscape rehabilitation may help alleviate the effects of past erosion and provide immediate benefits to the productivity of severely eroded soils. Core Ideas:  Replacing translocated topsoil can restore productivity to severely eroded land.  Adding 15 cm of topsoil increased corn and soybean grain yields by 12–59%.  Adding topsoil increased crop biomass but not emergence rates or stand establishment.  Adding topsoil did not significantly increase grain yield on moderately eroded land.  Areas of soil removal had lower crop yields, partially due to excessive moisture.